PEMANFAATAN APLIKASI CUSTOMERS RELATIONSHIP MANAGEMENT (CRM) BERBASIS MICROSERVICE PADA SISTEM INFORMASI KOPERASI - Yosafat Dony Kristovel; Marhaeni Marhaeni; Lely Mustika (JURNAL REKAYASA INFORMASI, 2022)
Cooperative is a business entity consisting of a person or a cooperative legal entity as well as a people's economic movement based on the name of kinship. However, due to the Covid-19 pandemic, traditional cooperative activities cannot be carried out either by cooperatives or cooperative members. The purpose of this research is to design and build applications that can help build cooperative applications to quickly obtain information on cooperative members in the Microservice-Based Customers Relationship Management (CRM) application in the Cooperative Information System. This research uses the observation method, and the latest literature study in using the data collection method, the design design system used in this research is the Javascript programming language and Node.js as the back-end language.